The drivers of ITIL adoption in UNITEN - Saleh J.M.; Almsafir M.K. (IEEE Computer Society, 2023)
In driving consistency, efficiency and excellence in managing IT services, Information Technology Infrastructure Library (ITIL) is identified to be the best mechanism. ITIL was introduced more than 20 years ago and since then the usage of ITIL in UK has extended into the private sectors, which include companies in Europe and the US. ITIL has become the most prominent method for IT Service Management worldwide. A study is being carried out in UNITEN, a private university in Malaysia to identify the main drivers for the adoption of ITIL. The purpose of this study is to find out the relationship between the drivers and the ITIL adoption in UNITEN. To accomplish this purpose, a set of questionnaire has been developed and distributed. The population for this study is the IT staff in the IT and Multimedia Services Department of UNITEN. Results show that the key performance indicator, intellectual capital and organization size (in terms of annual budget) are positively associated with the adoption of ITIL in UNITEN. The findings of this study would provide valuable information to UNITEN in further exercising ITIL best practices. 2013 IEEE.